2007
DOI: 10.1094/phyto-97-8-0916
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assay Using Mycelial Fragments to Assess Virulence of Mycosphaerella fijiensis

Abstract: We describe a method to evaluate the virulence of Mycosphaerella fijiensis, the causal agent of black leaf streak disease (BLSD) of banana and plantain. The method is based on the delivery of weighed slurries of fragmented mycelia by camel's hair brush to 5-by-5-cm areas on the abaxial surface of banana leaf blades. Reliable BLSD development was attained in an environmental growth chamber with stringent lighting and humidity controls. By localizing inoculum onto small areas of large leaves, we achieved a drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Twizeyimana et al (2007a) concluded that a GA 3 concentration of 5 mg L −1 is adequate to significantly reduce the chlorosis on banana leaf disks, but they observed only 52 days of incubation. Similar to a greenhouse test where successful disease development can take longer incubation period [2–3 months (Churchill 2010; Donzelli and Churchill 2007)], we have found that an 8 mg L −1 GA 3 supplement provides sufficient longevity for leaf disks to fulfill this condition without deteriorating. Although there are suggestions in other plant/fungus interactions (Takahashi et al 2005; Yamamoto et al 2000) that transgene expression just postpones symptom development and prolonging the incubation time results in similarly severe symptoms in transgenic plants as in non-transgenic controls, we observed this phenomenon only in the most susceptible transgenic line (GM.RCG3.09) during our LDA (up to 108 dpi).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Twizeyimana et al (2007a) concluded that a GA 3 concentration of 5 mg L −1 is adequate to significantly reduce the chlorosis on banana leaf disks, but they observed only 52 days of incubation. Similar to a greenhouse test where successful disease development can take longer incubation period [2–3 months (Churchill 2010; Donzelli and Churchill 2007)], we have found that an 8 mg L −1 GA 3 supplement provides sufficient longevity for leaf disks to fulfill this condition without deteriorating. Although there are suggestions in other plant/fungus interactions (Takahashi et al 2005; Yamamoto et al 2000) that transgene expression just postpones symptom development and prolonging the incubation time results in similarly severe symptoms in transgenic plants as in non-transgenic controls, we observed this phenomenon only in the most susceptible transgenic line (GM.RCG3.09) during our LDA (up to 108 dpi).…”
Section: Discussionsupporting
confidence: 66%
“…During the last decade, these bioassays became a useful tool for screening transgenic plants for disease resistance (Kumar et al 2003; Marchant et al 1998; Takatsu et al 1999). Two main categories of LDA can be distinguished, detached (Abadie et al 2009; Agnola et al 2003; Bussey and Stevenson 1991; Cohen 1993) and attached LDAs (Donzelli and Churchill 2007; Meeley et al 1992; Twizeyimana et al 2007a, b). In case of banana, rapid mass screening with attached leaves is difficult to carry out because of requirements in space and screenhouse conditions (e.g., high humidity and temperature) for efficient control of inoculations.…”
Section: Discussionmentioning
confidence: 99%
“…[40,41]), with development of disease symptoms not always correlating with those typically observed on intact plants. Additionally, [40] suggested that the hemibiotrophic Mycosphaerella banana pathogens require healthy banana plants for disease development, with [42] suggesting that the physiological state of detached leaves is not comparable with those on whole plants with an intact root system.…”
Section: Resultsmentioning
confidence: 99%
“…As we show in figure 5D, the mycelium of the dark strain ( Mf-1 , Figure S3) generates more 1 O 2 than the albino strain ( 102 , Figure S3); therefore 1 O 2 generation by melanin becomes a condition that causes oxidative stress and host cell death. Albino strains of M. fijiensis , compensate for melanin deficiency producing carotenes and higher catalase activitiy (unpublished results) and can infect banana leaves, but the damage is not so severe [21]. It has been long observed that banana plants infected with black Sigatoka are less severely affected in the shade than in full sunlight, suggesting the production of light activated toxins by these fungi.…”
Section: Discussionmentioning
confidence: 97%